Efficacy and toxicity of photon, proton, and carbon ion radiotherapy in the treatment of intracranial solitary fibrous tumor/hemangiopericytoma - Ton, Mike; Deng, Maximilian; Meixner, Eva; Eichkorn, Tanja; Krämer, Anna Sabrina; Seidensaal, Katharina; Hörner-Rieber, Juliane; Lischalk, Jonathan; Herfarth, Klaus; Debus, Jürgen; König, Laila (Radiation oncology, 2024)
Solitary fibrous tumors (SFT) of the central nervous system are rare and treatment options are not well established. The aim of this study was to evaluate the clinical outcomes of radiotherapy (RT) and re-radiotherapy (re-RT) for de novo intracranial SFT and recurrent intracranial SFT.